RESEARCH ON DOOR LIGHTWEIGHT BASED ON MODAL AND STIFFNESS - LIU Feng; ZHANG RuiQian; CHEN Yong (Jixie qiangdu)
Taking the left-front door of a certain vehicle as an object,the method of combining the welding plate and the adaptive response surface method（ ARSM） was applied to optimization of the thickness of door parts for lightweight research. The finite element model was established in Hyperworks and its modal and stiffness were analyzed. Then Hypermesh common-node model was used to simulate the laser tailor-welded technology,the front and rear parts of the original spot-welding door inner plate were connected by tailor-welded blank（ TWB） for optimal design. Through sensitivity analysis,some parts were selected to use adaptive response surface method in the Hyper Study for optimal design. The quality of the optimized door decreased by 6. 01%compared with the original ones. The modal and stiffness of the optimized door structure were analyzed again,The feasibility of TWB and Hyper Study optimization method to door lightweight research was verified.